SAE Technical Paper Series 2004
DOI: 10.4271/2004-01-0940
|View full text |Cite
|
Sign up to set email alerts
|

Boosting for High Load HCCI

Abstract: Homogeneous Charge Compression Ignition (HCCI) holds great promises for good fuel economy and low emissions of NO X and soot. The concept of HCCI is premixed combustion of a highly diluted mixture. The dilution limits the combustion temperature and thus prevents extensive NO X production. Load is controlled by altering the quality of the charge, rather than the quantity. No throttling together with a high compression ratio to facilitate auto ignition and lean mixtures results in good brake thermal efficiency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(41 citation statements)
references
References 17 publications
(17 reference statements)
0
41
0
Order By: Relevance
“…By boosting the engine in HCCI mode to extend the possible load range [12,13,14,15,16], the intake temperature will be elevated and can therefore be cooled down to a suitable level with an intercooler. The boost pressure can be controlled directly by the intake valve timing [16] which gives large freedom to operate the engine with optimum efficiency, emissions, combustion noise, cyclic variations and control strategies.…”
mentioning
confidence: 99%
“…By boosting the engine in HCCI mode to extend the possible load range [12,13,14,15,16], the intake temperature will be elevated and can therefore be cooled down to a suitable level with an intercooler. The boost pressure can be controlled directly by the intake valve timing [16] which gives large freedom to operate the engine with optimum efficiency, emissions, combustion noise, cyclic variations and control strategies.…”
mentioning
confidence: 99%
“…From Table 6 it can be observed that lower boost pressures and higher swirl ratios are favorable in mitigating the peak pressures. The peak pressures increase with increase in boost pressures irrespective of the swirl ratio, but the percentage increase in peak pressures is less at higher swirl ratios [33,34]. As swirl ratio increases; lower peak pressures are obtained at any boost pressure, but the percentage decrease in peak pressures is high at higher boost pressures.…”
Section: Boost Pressure (Bp)mentioning
confidence: 85%
“…Olsson et al [64] conducted experiments on a modified six-cylinder Scania D12 turbo charged diesel engine. The investigation studied the potential of high load HCCI through boost was evaluated and discussed, through simulations and in some cases supported by experiments.…”
Section: Effect Of Super Chargingmentioning
confidence: 99%